Effect of sulphate-reducing bacteria on the microbiologically influenced corrosion of ten different metals using constant test conditions. (November 2017) - Javed, M.A.; Neil, W.C.; McAdam, G.; Wade, S.A.
Abstract: Testing conditions have been shown to influence the outcomes of microbiologically influenced corrosion (MIC) studies. Despite this there are only limited reports comparing the performance of different metal types in MIC studies using exactly the same test conditions. This makes it difficult to predict the relative performance of different materials in applications in which MIC may occur. In the present work, the microbiologically influenced corrosion of a range of ferrous and non-ferrous alloys have been studied under identical test conditions. Metal coupons were exposed to a relatively common MIC test arrangement consisting of the sulphate-reducing bacterium, Desulfovibrio desulfuricans, in modified Baar's medium for a period of 90 days under anaerobic conditions. The results showed accelerated corrosion of carbon steel and copper-nickel alloys in the biotic test condition (i.e. with bacteria) compared to abiotic test conditions. No evidence of corrosion, however, was observed on any of the stainless steels, Inconel or titanium alloys in either of the abiotic or biotic test conditions studied. Highlights: MIC susceptibility of ten different metals was compared using a standard MIC test. Accelerated corrosion was observed for carbon steel and CuNi alloys with SRBs. No corrosion was found on any of the stainless steel, Inconel and titanium alloys.